1999
DOI: 10.5980/jpnjurol1989.90.692
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral Synchronous Multilocular Epididymal Cysts: A Case Report

Abstract: A rare case of bilateral synchronous multilocular epididymal cysts is reported. A fifty-six year old man visited to our hospital with a chief complaint of swelling of bilateral intrascrotal contents. Ultrasonographic findings demonstrated multilocular lesions of the bilateral intrascrotal contents. Preoperative diagnosis was bilateral multilocular hydrocele testes. Operative procedure revealed bilateral cysts originating from the head, body and tail of the epididymis without the cysts of the tunica vaginalis. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Preoperative diagnosis of bilateral multilocular hydrocele was made. 10 The epididymal cyst can be unilateral and unilocular or multilocular. These are commonly of less than 1cm in size.…”
Section: Discussionmentioning
confidence: 99%
“…Preoperative diagnosis of bilateral multilocular hydrocele was made. 10 The epididymal cyst can be unilateral and unilocular or multilocular. These are commonly of less than 1cm in size.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of either hydro or spermatocele diagnosed in specialized healthcare is approximately 100 per 100,000 men [ 9 ]. Bilateral epididymal cysts are significantly less frequent [ 4 ]. Multilocularity of epididymal cysts is rarer and rarely reported in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…Multilocularity of epididymal cysts is rarer and rarely reported in the literature. Only Ushida H et al [ 4 ] had reported multilocular bilateral synchronous epididymal cysts to date. Similar findings were noted in our case, too.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Simple cysts usually are small, approximately 1 cm in diameter, more frequently unilateral, uni- or multilocular, and located in the caput epididymis. Cysts in the corpus and cauda also have been reported [66]. Most cysts are asymptomatic, although larger ones may cause scrotal discomfort, pain, or present as a mass.…”
Section: Epididymal Anomaliesmentioning
confidence: 99%